The role of strong-tie social networks in mediating food security of fish resources by a traditional riverine community in the Brazilian Amazon - Mertens, Frédéric (2015)
Social networks are a significant way through which rural communities that manage resources under common property regimes obtain food resources. Previous research on food security and social network analysis has mostly focused on egocentric network data or proxy variables for social networks to explain how social relations contribute to the different dimensions of food security. Whole-network approaches have the potential to contribute to former studies by revealing how individual social ties aggregate into complex structures that create opportunities or constraints to the sharing and distribution of food resources. We used a whole-network approach to investigate the role of network structure in contributing to the four dimensions of food security: food availability, access, utilization, and stability. For a case study of a riparian community from the Brazilian Amazon that is dependent on fish as a key element of food security, we mapped the community strong-tie network among 97% of the village population over 14 years old (n = 336) by integrating reciprocated friendship and occupational ties, as well as close kinship relationships. We explored how different structural properties of the community network contribute to the understanding of (1) the availability of fish as a community resource, (2) community access to fish as a dietary resource, (3) the utilization of fish for consumption in a way that allows the villagers to maximize nutrition while at the same time minimizing toxic risks associated with mercury exposure, and (4) the stability of the fish resources in local ecosystems as a result of cooperative behaviors and community-based management. The contribution of whole-network approaches to the study of the links between community-based natural resource management and food security were discussed in the context of recent social-ecological changes in the Amazonian region.